Influence of Mentorship and the Working Environment on English as a Foreign Language Teachers’ Research Productivity: The Mediation Role of Research Motivation and Self-Efficacy - Li, Yanping; Zhang, Lawrence Jun (Frontiers in Psychology, 2022)
Research productivity is an important criterion for the university to assess teachers. Studies about factors that affect teachers’ research productivity are increasing nowadays. It is generally agreed that academics’ research productivity depends on how much mentorship is provided to them and how the current working environment is mediated by their research motivation and self-efficacy. Despite the increasing amount of the literature along this line, we know little about what kinds of situations that Chinese university English as a foreign language (EFL) teachers are in and how they regard the importance of mentorship and what roles their working environments would affect their research productivity. To fill the research gap, we utilized the snowball method to collect the survey data from 546 Chinese EFL tertiary teachers. The results show that mentorship is not correlated with research productivity while the working environment has a positive direct correlation with research productivity. Both motivation and self-efficacy mediate the working environment and research productivity significantly. Specifically, only extrinsic motivation has a negative mediation influence on teachers’ research productivity; teachers’ intrinsic motivation and self-efficacy play a positive mediation role on their research productivity.